Trust models and theories in human–computer interaction: A systematic literature review - Siddharth Gulati; Joe McDonagh; Sonia Sousa; David Lamas (Computers in Human Behavior Reports)
Trust in human–computer interaction (HCI) has been studied from multiple angles using a variety of theoretical frameworks. However, there is no comprehensive overview of these frameworks in the literature. We conducted a systematic literature review of 47 studies to establish a body of knowledge on trust frameworks in HCI. We found that 22 studies used theories from diverse fields such as psychology, economics, and communication to study trust formation and development. Our review highlights the challenge of capturing the dynamic nature of trust in HCI, given the complex interplay of multiple underlying factors. We also identify significant gaps in the current body of literature, highlighting the scarcity of standardized, empirically validated instruments for trust measurement. To address these issues, we propose avenues for future research, both theoretical and empirical. Furthermore, we emphasize the imperative of advancing new methods to capture better the multi-dimensional nature of trust. Our review contributes to broadening the discourse on trust in HCI, stimulating further inquiry and offering valuable insights for future research and practice.